Educating Financial Literacy: Mutual Funds Investment for Housewife (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This counseling is carried out to encourage financial literacy programs that are beneficial for improving the economy and community welfare. In addition, good literacy can prevent people from fake investment fraud. The researcher chose the mutual fund product because the investment is one of the capital market investment portfolios that can be purchased with an affordable nominal. This investment mix in the form of mutual funds offers attractive savings characteristics with varying risks depending on investor preferences. The webinar is conducted online with the aim of introducing the basics of investment, mutual fund characteristics, and several types of mutual funds. This introduction is expected to make the public better understand the concept of investment and savings, so that they can use the product wisely. From the webinar, researchers got a positive response that supports financial literacy and inclusion. The housewives participating in the webinar, who were previously unfamiliar with mutual fund investments, were actually very interested in trying to buy them. Mutual funds service providers, as well as the community.